Poisoning from wild mushrooms in Eastern Anatolia region: analyses of 5 years - Durukan, P.; Yildiz, M.; Cevik, Y.; Ikizceli, I.; Kavalci, C.; Celebi, S. (Sage Publications Ltd, 2007)
The objective of this study was to describe the demographic and clinical features of patients who were admitted to the emergency department (ED) due to wild mushroom poisoning and to point the importance of mushroom poisonings in our area. This study was performed by examining the files of wild mushroom poisoning patients who were admitted to the ED of Firat University, Faculty of Medicine, between January 2000 and June 2004, retrospectively. Patients :16 years of age were included in the study. The frequency of wild mushroom poisoning, age and sex of the patients, season, place of the residence, laboratory findings, treatment and outcome of the patients were investigated. During the study period, 64 patients with wild mushroom poisoning were admitted to the ED. From 64 overall patients, 25 (39.1%) were males. The most common complaints during the admission were nausea, vomiting and abdominal discomfort. The duration of hospitalization was two (range 1-4 days) days. No death was observed. Severity of mushroom poisoning depends on the type of mushroom eaten, the time lag between the poisoning and admission to the hospital, and the rapid and correct treatment given to the patient either in the ambulance or at health centre.
Keywords: emergency department; mushroom; poisoning